The Ascent of a leader - "Thrall, Bill."; "McNicol, Bruce.;McElrath, Ken." ("San Francisco, Calif. :")
Includes bibliographical references (p. 189-192) and index.
Keywords: LEADERSHIP -- RELIGIOUS ASPECTS.;CHARACTER -- RELIGIOUS ASPECTS.;SUCCESS -- RELIGIOUS ASPECTS.;SELF-REALIZATION -- RELIGIOUS ASPECTS